2004
DOI: 10.1093/rheumatology/keg468
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic dysfunction in primary Sjogren's syndrome

Abstract: Signs of an autonomic nervous system dysfunction involving the cardiovascular system can be discerned in the majority of pSS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 21 publications
3
18
1
2
Order By: Relevance
“…Recently, cardiovascular autonomic dysfunction in primary SS has been reported (46). Therefore, most likely in JHS as well as in primary SS, the decreased stimulation by the ANS of the salivary and lacrimal glands would produce xerophthalmia and xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cardiovascular autonomic dysfunction in primary SS has been reported (46). Therefore, most likely in JHS as well as in primary SS, the decreased stimulation by the ANS of the salivary and lacrimal glands would produce xerophthalmia and xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, autonomic neuropathy can be the presenting symptom of PSS [21,22]. In one series, cardiovascular dysautonomia was observed in the majority of PSS patients [23]. In another series, 50% of patients had autonomic symptoms and 69% had autonomic signs on testing [24].…”
Section: Autonomic Neuropathymentioning
confidence: 95%
“…Previous studies have shown a wide variation in the prevalence of sensorimotor polyneuropathy -6 [3 ], 23 [2], and 68% [15], although the motor fiber involvement in some of these studies may be ascribed to subclinical abnormalities seen on needle electromyography (EMG) or motor nerve conduction testing. The same is true for the high prevalence of pure motor neuropathy reported in other studies [5,16].…”
Section: Sensorimotor Polyneuropathy and Polyradiculopathymentioning
confidence: 99%
“…This is of clinical relevance because the diagnosis of small fibre neuropathy can usually only be proven by skin biopsies that show an increased intraepidermal nerve fiber density [47]. Most studies, with few exceptions [48], also depict an increased prevalence of autonomic symptoms in Sjögren's syndrome patients [46,[49][50][51].…”
Section: Sjö Gren's Syndromementioning
confidence: 99%